Social support-based self-management training for improving adherence among older adults with hypertension - Yulianti Maulidi; Suci Nugraha; Endah Nawangsih (Jurnal Psikologi Terapan dan Pendidikan, 2026)
Maintaining hypertension management among older adults remains a major challenge, particularly in maintaining medication adherence and sustaining healthy lifestyle behaviors. This study aimed to develop and validate a social support–based self-management training program designed to improve treatment adherence among older adults with hypertension. The study employed a mixed-methods Research and Development (R&D) design adapted from the Borg and Gall model, which was simplified into five stages: needs assessment, planning, product development, preliminary field testing, and revision. The study involved 10 older adults with hypertension who met the specified inclusion criteria. The findings indicated that the developed training module demonstrated satisfactory feasibility and initial validity based on expert evaluation and preliminary field testing. In addition, implementation of the training program was associated with improvements in participants’ adherence behaviors related to hypertension management. The integration of self-management strategies with social support mechanisms, including family involvement and caregiver support, contributed to strengthening participants’ behavioral awareness, motivation, and adherence to treatment routines. The findings also provide important theoretical and practical implications. Theoretically, this study supports the application of the biopsychosocial perspective and Social Cognitive Theory in understanding behavioral change among older adults with chronic illnesses. Practically, the developed module may serve as a structured educational intervention that can be implemented within primary health care settings to support sustainable hypertension management among older adults. Overall, these findings suggest that integrating self-management and social support represents a promising approach to improving treatment adherence among older adults with hypertension.